1973
DOI: 10.1021/j100631a027
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous thallium(I) metaborate and thallium(I) aluminum fluoride

Abstract: Mlile all the thallium (I) halides have been studied, 1 only two gaseous ternary compounds of monovalent thallium, thallium (I) nitrate 2 and thallium (I) sulfate, 3 have been reported so far. The purpose of this work was to extend the range of known gaseou5 ternary compounds of thallium (I) and to compare their mass spectrometric behavior to that of the corresponding alkali compm.mds. We have therefore examined the vapors above thallium (I) retaborate and an equimolar mixture of thallium (I) fluoride and alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In [68][69][70][71], it was demonstrated that the behavior of indium and thallium metaborates upon vaporization is…”
Section: Metaborates Of Periodicmentioning
confidence: 99%
“…In [68][69][70][71], it was demonstrated that the behavior of indium and thallium metaborates upon vaporization is…”
Section: Metaborates Of Periodicmentioning
confidence: 99%